Peningkatan Hasil Belajar PKn Siswa pada Materi Menghargai dan Menaati Keputusan Bersama dengan Menggunakan Metode Diskusi di Kelas V SDN. No. 017/XI Sungai Ning Tahun 2016/2017 - Misnawati Misnawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
This study is a classroom action research that aims to improve the learning outcomes of students of grade V SDN. No. 017 / XI Sungai Ning  year 2016/2017 on the subject of Civic Education, especially on respect and obey the mutual decisions by using discussion method. This research was conducted at SDN. No. 017 / XI Sungai Ning, Sungai Bungkal District, Sungai Penuh City, Jambi Province. The study was conducted from January to May 2017. The study involved six students of Grade V. Classroom action research was conducted in two cycles. Each cycle is done in two meetings with four activities, namely planning, implementation, observation, and reflection. Data was collected by observation and test. Data was processed and analyzed using descriptive analysis and simple statistical test. The results showed that the learning outcomes of students has increased. The average value of students who initially 48.33 increased to 63.33 in Cycle I, and again increased to 76.67 in Cycle II. Similarly, the percentage of learning mastery. the percentage of mastery learning students which initially 33.33% increased to 66.67% in Cycle I and again increased to 100.00% in Cycle II. Thus, the discussion method succeeded in improving the learning outcomes of students of grade V SDN. No. 017 / XI Sungai Ning year 2016/2017 on the subject of Civic Education, especially on respect and obey the mutual decisions.